KEABSAHAN HIBAH HARTA BERSAMA TANPA PERSETUJUAN SUAMI/ISTRI UNTUK PEMBANGUNAN KONSTRUKSI SARANA AIR MINUM - Alfan Perkasa Alam (2023)
This research discusses the legitimacy of joint property grants without the consent of the husband/wife for the construction of drinking water facilities and the legal consequences of land grants without the consent of the husband/wife for the construction of drinking water facilities. The purpose of this research is to find out the legitimacy of land grants without the consent of the husband/wife, as well as to find out the legal consequences of land grants without the consent of the husband/wife for the construction of drinking water facilities. The writing of this thesis was made using normative juridical research methods with statutory and case approaches. The results of the study show that, in implementing grants, the grantor must be legally competent and the land granted must be made a deed of grant by the PPAT so that it has legal force and as valid evidence. For cases of joint property grants, the validity must meet the existing requirements such as having the consent of the husband/wife. Otherwise, the grant becomes invalid. Prior to PP No. 24 of 1997, the grant deed had to be made in writing before a notary. Furthermore, after the birth of PP No. 24 of 1997 the deed of land and building grants must be carried out with a PPAT deed. So that for joint property grants obtained after marriage, the husband's/wife's consent is a condition that cannot be denied. This means that joint property cannot be contested as long as the marriage does not end due to divorce or death. So, if one of the parties takes an action related to the joint property, and one of the parties does not agree, then the grant cannot be made, if it is still carried out, the result will be null and void. So that the ownership of the donated property will return to the grantor and if the donated land has been certified in the name of the grantee, then the certificate is declared invalid.